Penggunaan Google Classroom dalam Pembelajaran untuk Meningkatkan Hasil Belajar Fisika - Amin, Nurul Fuad (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
The outbreak of the COVID-19 virus in Indonesia had resulted all activities having to be done at home. Therefore, the world of education must be able to create learning media that can be operated effectively from home. The problem of this research is the use of the Google classroom application in the physics learning process at SMAN 1 Sariwangi. The objectives to be achieved in this study are to identify and analyze the use of the Google Classroom application in the learning process. The research method used in this study is a qualitative research with descriptive methods. Data collection was conducted through interviews and observations. The subjects in this study were students of Class X IPA 1.The results showed that the Google Classroom application is a very flexible learning medium in place and time. The use of the google classroom application is also effective for distributing teaching materials and collecting assignments cause they use stationery. Any teacher can easily upload PowerPoints, videos and questions using Google Classroom. The conclusion of this research is that learning through the Google Classroom application is the right tool chosen for teachers, even though there are several obstacles that must be faced in the face of limited internet networks in some areas, the use of quotas, and at the same time the faciloties faced by some students